2015
DOI: 10.1371/journal.pone.0141469
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Components Influencing Colonization Factor Antigen I Expression in Enterotoxigenic Escherichia coli

Abstract: Colonization factors (CFs) mediate early adhesion of Enterotoxigenic Escherichia coli (ETEC) in the small intestine. Environmental signals including bile, glucose, and contact with epithelial cells have previously been shown to modulate CF expression in a strain dependent manner. To identify novel components modulating CF surface expression, 20 components relevant to the intestinal environment were selected for evaluation. These included mucin, bicarbonate, norepinephrine, lincomycin, carbon sources, and catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…The cfaABCE operon is positively regulated by the trans-encoded CfaD protein belonging to the family of AraC transcriptional regulators and negatively regulated by histone-like protein H-NS and cAMP receptor protein (CRP) (Caron and Scott, 1990 ; Jordi et al, 1992a ; Munson and Scott, 1999 ; Pilonieta et al, 2007 ; Bodero and Munson, 2009 ). In addition, several environmental factors of the intestinal lumen influence CFA/I expression including iron levels, pH, and gastric mucin (Haines et al, 2015 ). The etpBAC and cfaABCE operons are located on the same plasmid carried by ETEC and share inducing cues such as iron starvation.…”
Section: Discussionmentioning
confidence: 99%
“…The cfaABCE operon is positively regulated by the trans-encoded CfaD protein belonging to the family of AraC transcriptional regulators and negatively regulated by histone-like protein H-NS and cAMP receptor protein (CRP) (Caron and Scott, 1990 ; Jordi et al, 1992a ; Munson and Scott, 1999 ; Pilonieta et al, 2007 ; Bodero and Munson, 2009 ). In addition, several environmental factors of the intestinal lumen influence CFA/I expression including iron levels, pH, and gastric mucin (Haines et al, 2015 ). The etpBAC and cfaABCE operons are located on the same plasmid carried by ETEC and share inducing cues such as iron starvation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Sturbelle et al [88] did not observe any effect of norepinephrine or epinephrine on the in vitro growth of a piglet ETEC strain, and Haines et al [62] found a significant inhibition of porcine ETEC growth by norepinephrine. However, a significant increase in motility and expression of F4 fimbriae and LT toxin-encoding genes was shown in the ETEC culture supplemented with conditioned medium (containing autoinducers) and epinephrine [88].…”
Section: Host Hormonesmentioning
confidence: 94%
“…However, a significant increase in motility and expression of F4 fimbriae and LT toxin-encoding genes was shown in the ETEC culture supplemented with conditioned medium (containing autoinducers) and epinephrine [88]. Lastly, Haines et al [62] found that norepinephrine inhibited CFA/I expression in an ETEC strain isolated from humans.…”
Section: Host Hormonesmentioning
confidence: 99%
See 2 more Smart Citations